Improvement of Animal Manure by Mixing with Natural Zeolite - Lenny Marilyn Estiaty; Dewi Fatimah; Yoshiaki Goto (Jurnal Zeolit Indonesia, 2003)
Nowadays, Indonesia suffer a serious economic crisis. The situation is mainly caused by national industrial development strategy which is depend on import materials, e.g. in agriculture. In the cases, the national need are depend on import fertilizer, so that makes the national food stock become decreasing. This research is designed to offer another alternative in preparing and producing own fertilizer that we need, to solve the problem. New compotition of Animal manure has been made by addition of natural zeolite to gain a high nitrogen content. Characterisation analysis of materials included chemical composition of natural zeolite and manure fertilizer using AAS and Kyedhal analysis, structure analysis by XRD and SEM and CEC. The result of experiments showed that addition of natural zeolite to excrement (animal waste) increased the content of nitrogen and decreased the content of water in manure fertilizer. Ammonia absorption by natural zeolite with particle size of either "“8+14 or 14+20 mesh was almost similar. The nitrogen content of manure fertilizer which mixed with natural zeolite from kedung Banteng, Malang was bigger than that which mixed with natural zeolite from Cikancra, Tasikmalaya. The adsorbtion of water by natural zeolite of both particle sizes was also similar. Manure fertilizer which mixed with natural zeolite from Kedung Banteng was dryer than that which mixed with natural zeolite from Cikancra, Tasikmalaya. The improved animal manure has better properties like a high nitrogen content, dry and not malodorous.